2016
DOI: 10.1016/j.polymdegradstab.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hydrothermal aging of cycloaliphatic epoxy/graphene nanoparticle composites

Abstract: Cycloaliphatic epoxy (CE) resin systems are of primary interest in applications that require improved resistance to harsh conditions relative to other epoxy systems.Because other epoxy systems have demonstrated improved resistance to hydrothermal aging with the addition of carbon-based nanoparticle reinforcement, it is expected that the hydrothermal resistance of CE resins will likewise be improved with incorporation of nanoparticles. Therefore, the objective of this study is to determine the influence of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Figures and show that the addition of talc increases flexural modulus for all aging times, from 3.2 GPa for the neat epoxy to 4.1 GPa for the 20 wt% talc/epoxy composite. This is expected for reinforcement in epoxy and for talc in polymers in general . The trend from these data indicates that higher talc content leads to higher flexural modulus, but other studies with similar filler and epoxy systems indicate that there may be an optimal amount of talc above 20 wt% after which the modulus decreases .…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…Figures and show that the addition of talc increases flexural modulus for all aging times, from 3.2 GPa for the neat epoxy to 4.1 GPa for the 20 wt% talc/epoxy composite. This is expected for reinforcement in epoxy and for talc in polymers in general . The trend from these data indicates that higher talc content leads to higher flexural modulus, but other studies with similar filler and epoxy systems indicate that there may be an optimal amount of talc above 20 wt% after which the modulus decreases .…”
Section: Resultsmentioning
confidence: 56%
“…The final moisture content at 398 hr of aging was 3.2 wt% for the neat epoxy compared to 2.1 wt% for the 20 wt% talc composite. This is a dramatic improvement over previous aging research that used 2 and 4 wt% graphene nanoplatelets as a filler in a similar epoxy, where there were decreased moisture contents in the filled samples up to around 100 hr, but small/no differences at saturation . Starkova et al observed more significant impacts with thermally reduced graphene oxide (TRGO); water absorption decreased from about 5 wt% for unfilled epoxy to about 2 wt% for up to 0.5 wt% TRGO .…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations